Le Peuplement des Grassfields: recherches archeologiques dans l’ouest du Cameroun - Lavachery, Philippe (Afrika Focus, 1998)
Until recently the Grassfields (Western Cameroon), cradle of the Bantu languages, were an unknown zone from an archaeological point of view. The excavations of Shum Laka rock shelter offer the first chrono-cultural sequence for the area. After 20 millenniums of microlithic (Late Stone Age) traditions of hunter-gatherers, a new culture with macrolithic tools, pottery and arboriculture (Stone to Metal Age) slowly developed from 6000 BC onwards. Correlation with palaeo-climatic and historical linguistic data suggests that proto-Benue-Congo and, later, proto-Bantu speakers could have been involved in these industries. KEYWORDS: archeology, Cameroon, grassfields, proto-Bantu